Developing Interactive Learning Media Using Powtoon to Improve Students' Interest and Learning Outcomes in Global Warming Material - Puri Maharani; Desy Hanisa Putri (CV. Media Inti Teknologi, 2024)
The purpose of this study was to explain how well Powtoon Instructional Materials can help teachers carry out learning activities that can improve students' interest and learning outcomes on the topic of global warming. To explain how well Powtoon Instructional Materials can improve students' interest and learning outcomes. This study uses a type of development research commonly called Research and Development (R&D) with the ADDIE model (Analysis, Design, Development or Production, Implementation or Distribution, and Evaluation). 3 validators conducted validation to produce a feasible product, and the result was 87.6%, which indicates a very feasible category for use. According to the results of the distributed learning interest questionnaire, the initial results of the questionnaire were 55.2% for the low category and the final results were 73.4% for the moderate category. The pretest-posttest and N-Gain results were calculated to determine student learning outcomes. The calculation results show that the N-Gain score of 0.69 is in the moderate category and the N-Gain percentage of 69.5% is in the fairly effective category.